PRAGMATIC ROLES AND CONTEXTUAL USAGE OF ENGLISH AND UZBEK STRUCTURAL PARTS OF SPEECH - Xojibayeva Diyora Bakhtiyor qizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article is devoted to the study of the pragmatic features of structural parts of speech in English and Uzbek. The main purpose of the study is to determine the grammatical and context-dependent functions of structural parts of speech, to conduct a comparative analysis of their communicative and pragmatic role. Their in-depth study is of great practical importance for linguists, language learners.